EARTHQUAKE RECURRENCE INTERVAL BASED ON SEISMIC MOMENT - Massinai, Muhammad Fawzy Ismullah; Wijaya, Arif; Jamaluddin, Jamaluddin; Massinai, Muhammad Altin; Umar, Emi Prasetyawati; Minarti, Minarti (Universitas Mataram, 2021)
Indonesia is a country with high earthquake potential. This potential has been realized by its stakeholders and other parties. Various methods from many researchers from the fields of geophysics, geology, seismology, geodesy, geotechnical engineering, and others have been discussed to arrange earthquake mitigation. However, the discussions are unable to fit all earthquake mitigations across the country because they are still limited to specific characteristics of each fault among thousands of faults in Indonesia. Seismic moment is a parameter that provides information on the energy released when an earthquake occurs. This parameter, in any given scale, can provide information about the earthquake recurrence interval. The earthquake recurrence interval referred to here means that during a certain time period, the area under study has the possibility of experiencing an identical earthquake or with a smaller magnitude. This study tries to offer and test the method of calculating earthquake recurrence interval based on seismic moments. The method tested in several case studies of earthquakes in East Kalimantan has acceptable results. The method in this research has advantages value and can be alternative method in earthquake disaster mitigation.